Effects of acute predator odor exposure on paraventricular thalamus-central amygdala pathway activity in mice - LIU Chengyu; ZHAO Juanjuan; WANG Yaling; LI Siyu; XU Kan (陆军军医大学学报, 2022)
Objective To investigate the effects of acute exposure to predator odor (2, 4, 5-trimethylthiazole, TMT) on the activity of the paraventricular thalamic nucleus (PVT)-central amygdala (CeA) neural pathway in mice. Methods CTB555 was injected into CeA in 3 mice of the same lineage, and the neurons projected to CeA in the midline thalamus nuclei were observed. Eight male C57BL/6 mice were randomly divided into normal saline group and TMT group (exposed to predator odor), with 4 mice in each group. The effects of acute exposure to TMT on c-Fos expression in the midline thalamus nuclei and amygdala of mice were observed. Six mice of the same lineage were injected with RetroBeads in CeA, and then randomly and equally divided into normal saline group and TMT group. The effects of acute exposure to TMT on c-Fos expression in CeA projecting-PVT neurons were observed. The changes in calcium signals of CeA projecting-PVT neurons in vivo under acute exposure to TMT were recorded. AAV-EF1α-DIO-GCaMp7b was injected in PVT and AAV/retro-Syn-Cre was injected in CeA of 6 mice of the same lineage. In 3 weeks later, optical fiber was embedded above the injection site of PVT to in vivo record the changes in calcium signals of CeA projecting-PVT neurons before and after acute exposure to TMT. Results By injecting CTB555 into CeA, it was found that CeA selectively receives a large number of PVT projections in the midline thalamus nuclei. Compared with the control group, the expression of c-Fos in PVT (P < 0.01) and CeA (P < 0.05) was significantly increased after acute exposure to TMT. After injection RetroBeads in CeA, c-Fos expression in CeA projecting-PVT neurons was significantly enhanced after exposure to TMT (P < 0.05). Fiber photometry revealed that the ΔF/F values of CeA projecting-PVT neurons exposed to TMT were significantly higher than those exposed to normal saline (P < 0.01). Conclusion CeA projecting-PVT neurons are activated significantly after acute exposure to TMT.